A label‐free fluorescence method for detection of ureC gene and diagnosis of Helicobacter pylori infection. (21st May 2018) - Zhang, Leiyi; Cao, Ding; Tang, Tenglong; Zuo, Zhongkun; Huang, Jiangsheng; Duan, Lunxi
Abstract: The feasibility of using a polymerase chain reaction (PCR)‐based label‐free DNA sensor for the detection of Helicobacter pylori is investigated. In particular, H. pylori ureC gene, a specific H. pylori nucleic acid sequence, was selected as the target sequence. In the presence of ureC gene, the target DNA could be amplified to dsDNA with much higher detectable levels. After added the SYBR green I (SGI), the sensing system could show high fluorescence. Thus, the target DNA can be detected by monitoring the change of fluorescence intensity of sensing system. The clinical performance of this method was determined by comparing it with another conventional technique urea breath test (UBT). The result also showed good distinguishing ability between negative and positive patient, which was in good agreement with that obtained by the UBT. It suggests that the label‐free fluorescence‐based method is more suitable for infection confirmation test of H. pylori . This approach offers great potential for simple, sensitive and cost‐effective identification of H. pylori infection.